Noninvasive Follow-Up of Simian Immunodeficiency Virus Infection in Wild-Living Nonhabituated Western Lowland Gorillas in Cameroon - Etienne, Lucie (American Society for Microbiology, 2012)
Simian immunodeficiency viruses infecting western lowland gorillas (SIVgor) are closely related to HIV-1 and are most likely the ancestors of HIV-1 groups O and P. At present, limited data are available on genetic diversity, transmission, viral evolution, and pathogenicity of SIVgor in its natural host. Between 2004 and 2011, 961 putative gorilla fecal samples were collected at the Campo Ma'an National Park, Cameroon. Among them, 16% cross-reacted with HIV-1 antibodies, corresponding to at least 34 infected gorillas. Combining host genotyping and field data, we identified four social groups composed of 7 to 15 individuals each, with SIV rates ranging from 13% to 29%. Eleven SIVgor-infected gorillas were sampled multiple times; two most likely seroconverted during the study period, showing that SIVgor continues to spread. Phylogenetic analysis of partial env and pol sequences revealed cocirculation of closely related and divergent strains among gorillas from the same social group, indicating SIVgor transmissions within and between groups. Parental links could be inferred for some gorillas infected with closely related strains, suggesting vertical transmission, but horizontal transmission by sexual or aggressive behavior was also suspected. Intrahost molecular evolution in one gorilla over a 5-year period showed viral adaptations characteristic of escape mutants, i.e., V1V2 loop elongation and an increased number of glycosylation sites. Here we show for the first time the feasibility of noninvasive monitoring of nonhabituated gorillas to study SIVgor infection over time at both the individual and population levels. This approach can also be applied more generally to study other pathogens in wildlife.